Modulation of Cox-1, 5-, 12- and 15-Lox by Popular Herbal Remedies Used in Southern Italy Against Psoriasis and Other Skin Diseases - Bader, Ammar (2015)
Acanthus mollis (Acanthaceae), Achillea ligustica, Artemisia arborescens and Inula viscosa (Asteraceae) are used in Southern Italy against psoriasis and other skin diseases that occur with an imbalanced production of eicosanoids. We here assessed their in vitro effects upon 5-, 12-, 15-LOX and COX-1 enzymes as well as NFκB activation in intact cells as their possible therapeutic targets. All methanol crude extracts inhibited both 5-LOX and COX-1 activities under 200 μg/mL, without significant effects on the 12-LOX pathway or any relevant in vitro free radical scavenging activity. NFκB activation was prevented by all extracts but A. mollis. Interestingly, A. ligustica, A. arborescens and A. mollis increased the biosynthesis of 15(S)-HETE, an anti-inflammatory eicosanoid. A. ligustica (IC50 = 49.5 μg/mL) was superior to Silybum marianum (IC50 = 147.8 μg/mL), which we used as antipsoriatic herbal medicine of reference. Its n-hexane, dichloromethane and ethyl acetate fractions had also inhibitory effects on the LTB4 biosynthesis (IC50s = 9.6, 20.3 and 68 μg/mL, respectively) evidencing that the apolar extracts of A. ligustica are promising active herbal ingredients for future phytotherapeutical products targeting psoriasis.